Assessment of the effect of Metformin on the plasma LDL-C levels at T2DM patients - يوسف, رولا; رنا ماخوس; يونس قبلان (Latakia University Journal -Medical Sciences Series, 2023)
Type 2 diabetes is a chronic and progressive metabolic disease, associated with a significantly high risk of early atherosclerotic coronary heart disease. It is believed that the basic relation between diabetes and heart problems is due to Lipid disturbances (diabetic dyslipidemia). There are many evidences about the effect of metformin on blood lipids in addition to being a hypoglycemic agent. This study aimed to evaluate the effect of metformin on LDL-Cholesterol in patients with T2DM. The Multicenter Comparative (Before- After) Study was conducted at Al-Mouwasat and Al-Assad University Hospitals in addition to Al-Zahira Comprehensive Clinics Center in Damascus-Syria. The study included 56 patients (28 newly diagnosed with T2DM and 28 with pre-diabetes) who received metformin treatment. LDL-C values were measured before and three months after taking treatment. At the end of the study, there was a statistically significant decrease in LDL-C levels after treatment with metformin, P-value = 0.0001, and the percentage of decrease was estimated at 9.61%, but this effect wasn't dose-dependent. We noticed that metformin's ability to lower plasma LDL-C levels was not directly related to its ability to lower blood's glucose. Our study showed that metformin has a good positive effect on a risk indicator of atherosclerotic heart disease, which is LDL-C in patients with T2DM.